Anatomical Basis of Differences in Locomotor Behavior in Martens: A Comparison of the Forelimb Musculature Between Two Sympatric Species of Martes. Issue 3 (8th February 2018) - Böhmer, Christine; Fabre, Anne‐Claire; Herbin, Marc; Peigné, Stéphane; Herrel, Anthony
ABSTRACT: Arboreal locomotion imposes selective pressures that may affect the evolution of the locomotor apparatus. The limbs have to be mobile to reach across discontinuities, yet at the same time need to be forceful to move against gravity during climbing. However, as intermediaries between the arboreal and terrestrial environment, semi‐arboreal mammals appear not extremely specialized and, thus, anatomical adaptations may be less evident than expected for arboreal climbers. Here, we present quantitative data on the muscle anatomy of the forelimbs (N = 14) of two closely related species of Mustelidae and relate the findings to their locomotor habits. The arboreal pine marten ( Martes martes ) and the more terrestrial stone marten ( Martes foina ) are the most similar sympatric carnivores in Europe, but distinctly differ in habitat selection and locomotor mode. Via dissections muscle architectural variables including muscle mass, pennation angle, and fiber length were measured and the physiological cross‐sectional area and maximum isometric force were estimated for each muscle. The results reveal that the force‐generating capacity of the limb flexor and retractor muscles and the excursion capability of the adductor muscles are greater in the pine marten compared to the stone marten. Since the two sympatric martens are very similar in terms of overall appearance, body size, intra‐limb proportions, phylogenetic relationships and predation behavior, the differences in forelimb musculature are interpreted to reflect the greater climbing ability of the pine marten. The functional properties appear to facilitate locomotion in a three‐dimensionally complex arboreal environment. Anat Rec, 301:449–472, 2018. © 2018 Wiley Periodicals, Inc.